Teaching speaking in large classes: Crossing the barriers (Stamford Journal of English, 2013)
The modern theories, approaches and methodologies regarding classroom language learning perceive learning as an interactive process. In countries like Bangladesh, where English is a foreign language, one common phenomenon is that the teachers have to deal with large classes. This paper tries to focus on how the English language teachers deal with large classes at the tertiary level, especially when they are conducting classes to practice and evaluate speaking skills of students. A survey was conducted on 52 English language teachers working at different private universities to find out the problems teachers face when the carry on and observe speaking classes. The study finds that students less exposure to the real life interaction in the target language, their nervousness, influence of the L1, adverse social environment along with other problems tend to hamper the smooth ongoing of the class. But as most of the teachers consider large class as a challenge rather than a problem, so they attempt to utilize different new methods of teaching speaking in classrooms. The authors of this paper suggest some innovative techniques and methods found to be effective and fruitful in large classes. Stamford Journal of English; Volume 6; Page 72-89 DOI: http://dx.doi.org/10.3329/sje.v6i0.13904